Implementation of Six Sigma in service industry - Aminudin Omar,; Zainol Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2014)
As providing high quality services becomes the major focus in many service organisations, a better understanding of the unique characteristics of services offered will be of advantage. This in turn will help assist in identification of areas to improve by implementation of quality program initiatives such as Six Sigma in such organisation. Many service processes are not visible, intangible, and even immeasurable. As such, they are not amendable to improvement using a Six Sigma approach. This thinking has turned out to be rather presumptuous at least for the health care, banking, and call centre services which have successfully implemented Six Sigma in their daily operations. Other services such as education and hospitality are also beginning to apply Six Sigma quality initiatives. This paper provides summary of limitations and suggestions for implementation of Six Sigma in the service industries